Maritime Medicine, Hyperbaric and Emergency Case in The Future - Hisnindarsyah (Asian Journal of Health Research, 2024)
The future of maritime medicine holds promising advancements, driven by technological innovation, enhanced training protocols, and a deeper understanding of the unique challenges faced by seafarers. Here's a glimpse into what the future might hold advanced telemedicine capabilities will enable real-time consultations between maritime healthcare providers and specialists onshore. Wearable devices and sensors will allow continuous monitoring of crew members' health parameters, facilitating early detection of illnesses or injuries.